The Expanding Scope of Nursing: Integrating Evidence-Based Practice, Technology, and Compassionate Care in the 21st Century - Alshammari, Mutera Ghafel; Alrubaie, Ahlam Saad; Alrasheed, Reem Saeed; Alosimi, Muneerah Faheed; Alanazi, Bashayr Mohammed; Alanzi, Amjad Obaid; Alshahrani, Ashwag Muneef; Alamri, Rana Saeed; Alshahrani, Fatima Mohammed Ali (Journal of Posthumanism, 2024)
Nursing in the 21st century is undergoing a profound transformation, expanding beyond its traditional caregiving role to embrace evidence-based practice, advanced technologies, and sustained compassionate care. This integrative review explores the evolving scope of nursing across five research dimensions: the role of evidence-based practice in improving patient outcomes, the integration of digital health technologies into nursing practice, the preservation of compassion and human connection in an increasingly technological environment, the challenges and barriers faced by the profession, and the implications for education, policy, and practice. Findings indicate that while evidence-based practice and technological tools enhance efficiency, safety, and standardization, the essence of nursing continues to depend on humanistic values that foster trust and empathy. However, barriers such as workforce shortages, ethical dilemmas, unequal access to resources, and resistance to change hinder the full realization of nursing’s potential. The review concludes that the future of nursing lies in a balanced model that integrates science, innovation, and compassionate care, supported by progressive policies and continuous professional development. This holistic approach will ensure that nursing remains a cornerstone of healthcare transformation and patient-centered care in the modern era.